Ferulic acid esterase-producing lactic acid bacteria and cellulase pretreatments of corn stalk silage at two different temperatures: Ensiling characteristics, carbohydrates composition and enzymatic saccharification. (June 2019) - Li, Fuhou; Ding, Zitong; Ke, Wencan; Xu, Dongmei; Zhang, Ping; Bai, Jie; Mudassar, Shah; Muhammad, Ishaq; Guo, Xusheng
Highlights: Lp A1 could enhance the ensilage process and enzymatic saccharification. Pretreatment with Lp A1 could reduce the fiber content of corn stalk silage. Cellulose + Lp A1 had better performance in reducing lignocellulose. Lp A1 had better performance in reducing lignocellulose at 25 °C rather than 40 °C. Abstract: The effects of Acremonium cellulase and L. plantarum A1 with ferulic acid esterase activity on corn stalk silage fermentation characteristics, carbohydrate composition and enzymatic saccharification were studied at 25 and 40 °C, respectively. Corn stalk was ensiled without additive (C), Acremonium cellulase (AC), L. plantarum A1 (Lp) and AC + Lp for 60 days. Pretreatment with Lp or AC + Lp promoted the better silage fermentation and the degradation of lignocellulose as indicated by high lactic acid and low pH and lignocellulose content compared to control silages at 25 °C. AC + Lp performed better in reducing lignocellulose and DM loss. In addition, Lp alone enhanced enzymatic saccharification of corn stalk silage. However, the influence of L. plantarum A1 on corn stalk silage was not obvious at 40 °C. Corn stalk ensiled with combined additive is a suitable pretreatment method for subsequent biofuel production at 25 °C, but addition of Acremonium cellulase alone at 40 °C may be a promising method.